2001
DOI: 10.1530/rep.0.1210685
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian aromatases

Abstract: Aromatase is the enzyme complex that catalyses the synthesis of oestrogens from androgens, and therefore it has unique potential to influence the physiological balance between the sex steroid hormones. Both aromatase cytochrome P450 (P450arom) and NADPH-cytochrome P450 reductase (reductase), the two essential components of the enzyme complex, are highly conserved among mammals and vertebrates. Aromatase expression occurs in the gonads and brain, and is essential for reproductive development and fertility. Of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(106 citation statements)
references
References 20 publications
4
99
0
3
Order By: Relevance
“…In other study, cytochrome enzymes P450c17 and P450 aromatase were found in vaginal tissue throughout estrous cycle suggesting a local production of androgen and estrogen hormones (Santos et al, 2014b) in agreement with several studies that have shown a wide variety of different production sites of steroid hormones in different mammalian species (Conley and Hinshelwood, 2001;Conley et al, 2004).…”
Section: Introductionsupporting
confidence: 91%
“…In other study, cytochrome enzymes P450c17 and P450 aromatase were found in vaginal tissue throughout estrous cycle suggesting a local production of androgen and estrogen hormones (Santos et al, 2014b) in agreement with several studies that have shown a wide variety of different production sites of steroid hormones in different mammalian species (Conley and Hinshelwood, 2001;Conley et al, 2004).…”
Section: Introductionsupporting
confidence: 91%
“…P450arom is present in the ER of numerous vertebrate tissues and has been the focus of studies in numerous species (Conley & Hinshelwood 2001). According to Carreau et al (1999) and Hess et al (2001), the primary source of estrogen is the Sertoli cell in the immature testis and Leydig and germ cells in the mature testis.…”
Section: Expression Of Steroidogenic Enzymesmentioning
confidence: 99%
“…1 The balance of androgen and oestrogen X. Li et al localization and the different 5 0 UTR CYP19A1 variants, each transcript generates a highly conserved 55 kDa aromatase protein [17]. Thus, the spatio-temporal expression of CYP19A1 is critical for the maintenance of the oestrogen/androgen balance during foetal and postnatal development.…”
Section: Aromatase and Its Expression In Malesmentioning
confidence: 99%